EFFECT OF MIXED CROPPING IN POTATO ON SURVIVAL AND PERPETUATION OF R. SOLANACEARUM CAUSAL AGENT OF BACTERIAL WILT OF POTATO - Venkatesh, Venkatesh; Indiresh, K M; Patil, S. V.; Siddagangaiah, Siddagangaiah (Potato Journal, 2013)
Bacterial wilt of potato caused by Ralstonia solanacearum (Smith) Yabuuchi et al. is a serious disease, causing enormous loss to the farmers. The disease is most destructive and widespread in Karnataka and causes up to 75% loss in yield in some localities of Karnataka. Presently, to manage the disease under rainfed situation of southern transitional zone of Karnataka, the integrated management practices namely (1) Crop rotation with finger millet, (2) Fall ploughing and (3) Application of bleaching powder @ 15 kgs/ha, are recommended. However, these strategies are effective in monocrop situation, while in mixed cropping system, effectiveness of the integrated practices varies. Three-year field trials were conducted during 2002-04 to study the effect of mixed cropping in potato on survival and perpetuation of R. solanacearum-causal agent of bacterial wilt. It was revealed that maximum disease incidence of 56.64, 64.16 and 65.40 per cent was recorded in mixed cropping i.e., potato + castor (long duration var.) compared to monocrop of potato (33.30, 27.75 and 24.20 per cent disease) during 2002, 2003 and 2004 trials, respectively. Disease incidence in potato + beans and potato + maize was less as compared to monocrop of potato. Correspondingly, maximum pathogen population in rhizosphere and soil was recorded in potato + castor (long duration var.) mixed cropping system compared to monocrop of potato and other mixed cropping systems.